Production, Reproduction, and Commodification of Historical Knowledge in Medan in Digital Media and Commercial Practices - Nababan, Surya Aymanda; Hasudungan, Anju Nofarof (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
This study examines the transformation of historical knowledge in Medan City through the interrelated dimensions of production, reproduction, and commodification within a contemporary context. The expansion of digital media and the creative economy has displaced the exclusive authority of academic institutions, enabling historical knowledge to circulate through non-academic actors, institutional platforms, and commercial practices. Employing a qualitative design, the research utilizes critical discourse analysis to investigate digital content on YouTube and Instagram, alongside commercial representations of Medan’s history, with a focus on content creators, government-managed accounts, and the local culinary industry as primary empirical sites. The analytical framework integrates Michel Foucault’s concept of power–knowledge relations and Pierre Bourdieu’s notions of habitus and cultural capital, allowing for a nuanced interpretation of how authority and meaning are negotiated. The findings indicate a decentralisation of epistemic authority, wherein historical narratives are increasingly shaped by visuality, participation, and popular mediation, thereby cultivating new forms of habitus in the public understanding of the past. This transformation reconfigures the epistemic structure of history, blurs the boundary between intellectual and popular history, and calls for sustained interdisciplinary engagement to safeguard scientific integrity.